The Single Leg Squat Test: A "Top-Down" or "Bottom-Up" Functional Performance Test? - Lindsay A Carroll; Benjamin R Kivlan; RobRoy L Martin; Amy L Phelps; Christopher R Carcia (North American Sports Medicine Institute, 2021)
# Background Medial knee deviation (MKD) during the single leg squat test (SLST) is a common clinical finding that is often attributed to impairments of proximal muscular structures. Investigations into the relationship between MKD and the foot and ankle complex have provided conflicting results, which may impact clinicians' interpretation of the SLST. # Purpose The purpose of this study was to compare ankle dorsiflexion range of motion (ROM) and foot posture in subjects that perform the SLST with MKD (fail) versus without MKD (pass). # Hypothesis There will be a difference in ankle dorsiflexion ROM and/or foot posture between healthy individuals that pass and fail the SLST for MKD. # Study Design Cross-sectional study. # Methods Sixty-five healthy, active volunteers (sex = 50 female, 15 male; age = 25.2 +/- 5.6 years; height = 1.7 +/- .1 m; weight = 68.5 +/- 13.5 kg) who demonstrated static balance and hip abductor strength sufficient for performance of the SLST participated in the study. Subjects were divided into pass and fail groups based on visual observation of MKD during the SLST. Foot Posture Index (FPI-6) scores and measures of non-weight bearing and weight bearing active ankle dorsiflexion (ROM) were compared. # Results There were 33 individuals in the pass group and 32 in the fail group. The groups were similar on age (p = .899), sex (p = .341), BMI (p = .818), and Tegner Activity Scale score (p = .456). There were no statistically significant differences between the groups on the FPI-6 (pass group mean = 2.5 +/- 3.9; fail group mean = 2.3 +/- 3.5; p = .599), or any of the measures of dorsiflexion range of motion (non-weight bearing dorsiflexion with knee extended: pass group = 6.9^o^ +/- 3.7^o^, fail group = 7.8^o^ +/- 3.0^o^; non-weight bearing dorsiflexion with knee flexed: pass group = 13.5^o^ +/- 5.6^o^, fail group = 13.9^o^ +/- 5.3^o^; weight bearing dorsiflexion: pass group = 42.7^o^ +/- 6.0^o^, 42.7^o^ +/- 8.3^o^, p = .611). # Conclusions Failure on the SLST is not related to differences in clinical measures of active dorsiflexion ROM or foot posture in young, healthy individuals. These findings suggest that clinicians may continue using the SLST to assess neuromuscular performance of the trunk, hip, and knee without ankle dorsiflexion ROM or foot posture contributing to results. # Level of Evidence Level 3.